Implementation of principal leadership, the role of school committees, and their impacts on the success of school-based management - Pujiyati, Wresni; Senjaya, Dian Yudiana (Indonesian Research Journal in Education |IRJE|, 2025)
This research aimed to determine and analyze the influence of the implementation of principal leadership and the role of the school committee on the success of school-based management, both partially and multiplicatively. This research used a survey method with a quantitative approach, as well as correlational and regression techniques. The respondents in this research were teachers at public elementary schools. Based on the research results, the researchers suggest (1) that from the planning and implementation to the reporting, the principal should involve teachers and be open and transparent so that teachers can know the progress of school operations. Because all programs are known to all teachers, it is hoped that the value of honesty can be achieved. (2) Input should be requested from the school committee to be included in the academic aspect program so that the school committee plays a greater role in facilitating school operations through school-based management.